How to have an effective online teamwork training, engaging employees through a supportive environment, in times of Covid-19 - Valenza, Ilaria (2022)
Nowadays online training is becoming crucial in employee’slife, this phenomenon already started in the last decade, however due to the current pandemic situation, companies had to improve and to update their tools to provide efficient training even during lockdown. This cross-sectional study (N=200) aims to identify the elements that, in online training settings, can be applied to implement the effectiveness of the training. We hypothesized that interactivity, as a characteristic of training, was positively related to the effectiveness of online teamwork training. Therefore, we supposed that a supportive working environment was positively connected to the efficacy of the training process. A regression analysis between those variables demonstrated the existence of these relations. Moreover, we hypothesized that the variable engagement was working as a mediator between interactivity and the effectiveness of training, but also between the variable supporting working environment and the training efficacy. The mediation model supported these hypotheses though with some limitations. Further, we discuss the practical implications of these findings and suggest directions for future research.